Interaction between bisphenol A and dietary sugar affects global gene transcription in Drosophila melanogaster - Alan T. Branco; Bernardo Lemos (Genomics Data, 2014)
Human exposure to environmental toxins is a public health issue. The microarray data available in the Gene Expression Omnibus database under accession number GSE55655 and GSE55670 show the isolated and combined effects of dietary sugar and two organic compounds present in a variety of plastics [bisphenol A (BPA) and Bis(2-ethylhexyl) phthalate (DEHP)] on global gene expression in Drosophila melanogaster. The study was carried out with samples collected from flies exposed to these compounds for a limited period of time (48 h) in the adult stage, or throughout the entire development of the insect. The arrays were normalized using the limma/Bioconductor package. Differential expression was inferred using linear models in limma and BAGEL. The data show that each compound had its unique consequences to gene expression, and that the individual effect of each organic compound is maximized with the joint ingestion of dietary sugar.